A Rehabilitation of Monetary Policy in the 1950's - Romer, Christina D; Romer, David H (American Economic Review, 2002)
Monetary policy in the United States in the 1950s was remarkably modern. Analysis of Federal Reserve records shows that policymakers had an overarching aversion to inflation and were willing to accept significant costs to prevent it from rising to even moderate levels. This aversion to inflation was the result of policymakers' beliefs that higher inflation could not raise output in the long run, that the level of output that would trigger increases in inflation was only moderate, and that inflation had large real costs in the medium and long runs. Furthermore, both narrative and empirical analysis indicates that policymakers were not wedded to free reserves or other faulty indicators in their implementation of policy. Empirical estimates of a forward-looking Taylor rule show that policymakers in the 1950s raised nominal interest rates more than one-for-one with increases in expected inflation, and suggests that monetary policy in the 1950s was more similar to policy in the 1980s and 1990s than to that in the late 1960s and 1970s. One implication of these findings is that the inflation of the late 1960s and 1970s must have been the result of a change in the conduct of policy.